Formation of silver and gold nanoclusters supported on thin silica films and mordenites; XV International Symposium on Small Particles and Inorganic Clusters, Oaxaca City, Mexico, 19-24 September, 2010 - Kovalenko D.; Gurin V.; Bogdanchikova N.; Petranovskii V.; Tuzovskaya I.; Pestryakov A. N. Aleksey Nikolaevich (2010, 2010)
В фонде НТБ ТПУ отсутствует